2019
DOI: 10.1088/1755-1315/359/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of Acacia mangium provenances in Parung Panjang, Bogor and its correlation with physical and mechanical wood properties

Abstract: Wood quality and growth are two important parameters that need to be analyzed for the utilization and selection of superior genotypes. The objective of this research was to investigate the ten provenances growth characteristics and their physical and mechanical properties of Acacia mangium at Parung Panjang, Bogor. The provenance trial was arranged in three blocks of a randomized completely blocks design. In every provenance, 18 trees were sampled resulting in a total of 180 trees in each block representing ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…The research by Nugroho et al (2011) explained that the average values in jabon aged 7 years were 651 x 10 2 kgcm -² and 601 kgcm -². Meanwhile, the values for A. mangium aged 10 years were 89814.4 kgcm -² and 651.97 kgcm -² (Nurhasybi and Sudrajat 2019). This study's MOE and MOR values were lower than those of jabon and A. mangium, aged 7 and 10 years.…”
Section: Physical Properties Of Woodcontrasting
confidence: 57%
See 1 more Smart Citation
“…The research by Nugroho et al (2011) explained that the average values in jabon aged 7 years were 651 x 10 2 kgcm -² and 601 kgcm -². Meanwhile, the values for A. mangium aged 10 years were 89814.4 kgcm -² and 651.97 kgcm -² (Nurhasybi and Sudrajat 2019). This study's MOE and MOR values were lower than those of jabon and A. mangium, aged 7 and 10 years.…”
Section: Physical Properties Of Woodcontrasting
confidence: 57%
“…Several studies have shown intraspecific variation in the wood quality of tree species, such as in Picea glauca (Moench) Voss (Lenz et al 2013), Acacia mangium Willd. (Nurhasybi and Sudrajat 2019), and Swietenia macrophylla G.King (Sudrajat et al 2021). Therefore, more comprehensive information on the basic properties of wood in the provenance level of jabon is critical to obtain superior provenances based on the quality of the wood.…”
Section: Introductionmentioning
confidence: 99%
“…Nugroho et al (2011) found that the average MOE and MOR values at the age of 7 years were 65100 kg/cm² and 631 kg/cm², respectively. As comparison, the MOE and MOR values for Acacia mangium at the age of 10 years old were 89814.4 kg/cm² and 651.97 kg/cm², respectively (Nurhasybi and Sudrajat 2019). The MOE and MOR values of the study are lower than the 7-year-old N. cadamba and 10-year-old A. mangium.…”
Section: Discussionmentioning
confidence: 61%